Plant nucleolar DNA: Green light shed on the role of Nucleolin in genome organization. (2nd January 2017) - Picart, Claire; Pontvianne, Frédéric
ABSTRACT: The nucleolus forms as a consequence of ribosome biogenesis, but it is also implicated in other cell functions. The identification of nucleolus-associated chromatin domains (NADs) in animal and plant cells revealed the presence of DNA sequences other than rRNA genes in and around the nucleolus. NADs display repressive chromatin signatures and harbour repetitive DNA, but also tRNA genes and RNA polymerase II-transcribed genes. Furthermore, the identification of NADs revealed a specific function of the nucleolus and the protein Nucleolin 1 (NUC1) in telomere biology. Here, we discuss the significance of these data with regard to nucleolar structure and to the role of the nucleolus and NUC1 in global genome organization and stability.